Pengaruh Penggunaan Alokasi Dana Desa (ADD), Akuntabilitas dan Transparansi Pengelolaan Keuangan Desa Terhadap Kesejahteraan Masyarakat (Studi Pada Desa Jambu Kecamatan Mlonggo Kabupaten Jepara) - Afista Nur Khasanah; Ichwan Marisan (Jurnal Rekognisi Akuntansi, 2022)
This study aims to determine the effect of using village fund allocation, accountability and transparency of village financial management on the welfare of the community in Jambu Village, Mlonggo District, Jepara Regency. This research is a quantitative research. The sample used to conduct this study was obtained using a purposive sampling method based on predetermined criteria, namely the people of Jambu Village, Mlonggo District, Jepara Regency who have a productive age between 20-60 years, last high school education, and have a permanent job. The number of samples used as many as 100 respondents . The method of analysis in this study is using multiple linear regression analysis. The results showed that the variable of using village fund allocation had a negative effect on the welfare of the Jambu Village community with a significant value of 0.804, the accountability variable had a significant positive effect on the welfare of the Jambu Village community with a significant value of 0.000, the village transparency variable had a negative effect on the welfare of the Jambu Village community with a negative value of significant at 0, 225, the use of village fund allocation, accountability, transparency has a significant positive effect on the welfare of the Jambu Village community with a significant value of 0.000.